2018
DOI: 10.3847/1538-3881/aac894
|View full text |Cite
|
Sign up to set email alerts
|

Zodiacal Exoplanets in Time (ZEIT). VII. A Temperate Candidate Super-Earth in the Hyades Cluster

Abstract: Transiting exoplanets in young open clusters present opportunities to study how exoplanets evolve over their lifetimes. Recently, significant progress detecting transiting planets in young open clusters has been made with the K2 mission, but so far all of these transiting cluster planets orbit close to their host stars, so planet evolution can only be studied in a high-irradiation regime. Here, we report the discovery of a long-period planet candidate, called HD 283869 b, orbiting a member of the Hyades cluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 109 publications
1
27
0
Order By: Relevance
“…By observing fields across the ecliptic, K2 can study stars both near the galactic plane, where many young stars can be found, and the older stars a few scale heights away. K2 also has observed (and discovered planets in) several nearby open clusters and associations (Obermeier et al 2016;Mann et al 2016;Rizzuto et al 2018;Livingston et al 2018c;Vanderburg et al 2018). K2's observational breadth could enable determining occurrence rates for planets around different stellar populations and in different galactic environments, a key to understanding how and why planets form.…”
Section: Introductionmentioning
confidence: 90%
“…By observing fields across the ecliptic, K2 can study stars both near the galactic plane, where many young stars can be found, and the older stars a few scale heights away. K2 also has observed (and discovered planets in) several nearby open clusters and associations (Obermeier et al 2016;Mann et al 2016;Rizzuto et al 2018;Livingston et al 2018c;Vanderburg et al 2018). K2's observational breadth could enable determining occurrence rates for planets around different stellar populations and in different galactic environments, a key to understanding how and why planets form.…”
Section: Introductionmentioning
confidence: 90%
“…Our period measurement, P = 25.0 +49.8 −0.1 days, is compatible with both. Vanderburg et al (2018) estimate the period of EPIC 248045685b by a very similar method to ours, also exploiting information from the host star's Gaia parallax and public broadband photometry. They conclude that P = 106 +74 −26 days, and we agree, with P = 118 +119 −41 days.…”
Section: Comparison To Previous Workmentioning
confidence: 99%
“…The prospects for these types of studies have been greatly enhanced by recent discoveries of transiting planets around young stars. Data from the NASA K2 mission have been used to find planets in the 10-Myr-old Upper-Sco moving group (Mann et al 2016b;David et al 2016), the 20-Myr-old Taurus-Auriga group (David et al 2019), and older clusters such as Praesepe and the Hyades (e.g Mann et al 2016aMann et al , 2017Vanderburg et al 2018;Rizzuto et al 2018). These efforts have also resulted in the first determinations of the occurrence rates of close-in small planets in young associations and clusters, and allowed meaningful comparisons with the planet population around mature mainsequence field stars (Rizzuto et al 2017).…”
Section: Introductionmentioning
confidence: 99%